Universiti Utara Malaysia (UUM) students’ perception on national security policy: The case of Internal Security Act (ISA) of Malaysia - Mohd Sani, Mohd Azizuddin; Abdul Aziz, Abdul Rahman (Institute of Tun Dr. Mahathir Mohamad’s Thoughts, Universiti Utara Malaysia, 2010)
This study aims to examine the perception of the Internal Security Act (ISA) of Malaysia, focusing on the perceptions of students of Universiti Utara Malaysia. This study tries to determine the student’s perceptions first on the students’ comprehension of Malaysia’s national security policy in which constituted in the Malaysian Constitution and consequently understand its effect on the student’s reaction or attitude. The study is conducted using a questionnaire survey, consisting of statements in which the students were required to rate their response on a 5-point Likert scale. The questionnaire also consists of four main sections in which the demography of students, the evaluation of students perception on current national security threats in Malaysia, sets of statements in which testing the students’ basic comprehension of the ISA of Malaysia and fi nally their reactions towards the ISA itself. The finding indicates that the students are prone to social issues in which they determine it could be the major threat to Malaysia. Yet, there is no connection between comprehensions of the ISA and the reactions on the enforcement of the policy. Nevertheless, findings reveal their reactions differ between programmes of study and more inclined towards supporting the ISA and they also agree that government should take into consideration critics by the non-governmental organizations as well as societal grievances.